Characterization of endogenous bile acid composition in individuals with cold-activated brown adipose tissue. (1st October 2021) - Herz, Carsten T.; Kulterer, Oana C.; Prager, Marlene; Langer, Felix B.; Prager, Gerhard; Marculescu, Rodrig; Fauler, Günter; Hacker, Marcus; Kautzky-Willer, Alexandra; Trauner, Michael; Haug, Alexander R.; Kiefer, Florian W.
Abstract: Introduction: Bile acid signaling has been suggested to promote BAT activity in various experimental models. However, little is known if and how physiologic bile acid metabolism is linked to BAT function in humans. Here we investigated the association between BAT activity and circulating bile acid concentrations in lean and obese individuals. Methods: BAT 18 F-fluorodeoxyglucose uptake was measured after a standardized cooling protocol by positron emission tomography/computed tomography. Cold-induced thermogenesis was assessed by indirect calorimetry. Fasting bile acid concentrations were determined by high performance liquid chromatography–high-resolution mass spectrometry. Results: In a cohort of 24 BAT-negative and 20 BAT-positive individuals matched by age, sex, and body mass index, circulating bile acid levels were similar between groups except for higher ursodeoxycholic acid and a trend towards a lower 12α-OH/non-12α-OH bile acid ratio in lean participants with active BAT compared to those without. Moreover, the 12α-OH/non-12α-OH ratio, a marker of CYP8B1 activity, correlated negatively with BAT volume and activity. Conclusion: Fasting concentrations of major bile acids are not associated with cold-induced BAT activity in humans. However, the inverse association between BAT activity and 12α-OH/non-12α-OH ratio may suggest CYP8B1 as a potential new target in BAT function and warrants additional investigation.